Contributions of Loss of Lung Recoil and of Enhanced Airways Collapsibility to the Airflow Obstruction of Chronic Bronchitis and Emphysema - Leaver, D. G. (1973)
We investigated the contributions of intrinsic disease of the airways, loss of lung recoil and enhanced airway collapsibility to the airflow obstruction of 17 patients with chronic bronchitis and emphysema. Airways conductance at low flow (G(aw)), maximum expiratory flow (V̇(E, MAX)) and static lung recoil pressure [P(st) (l)] were measured at different lung volumes, and conductance-static recoil pressure and maximum flow-static recoil pressure curves constructed. Low values of ΔG(aw)/ΔP(st) (l) and ΔV̇(E), max/ΔP(st) (l) were attributed to intrinsic airways disease. Airway collapsibility was assessed by comparing G(aw) with upstream conductance on forced expiration and by the intercept of the maximum flow-static recoil curve on the static recoil pressure axis (P(tm)′). All patients had reduced G(aw) at all volumes but in seven ΔG(aw)/ΔP(st) (l) was normal. On forced expiration, maximum flow in all patients was reduced more than could be accounted for by loss of lung recoil. ΔV̇(E, MAX)/ΔP(st) (l) was reduced in the patients in whom ΔG(aw)/P(st) (l) was low. In contrast ΔV̇(E, MAX)/ΔP(st) (l) was normal in three and only slightly reduced in another three of the seven patients with normal ΔG(aw)/ΔP(st) (l). In these patients G(aw) greatly exceeded upstream conductance and P(tm)′ was increased. We conclude that loss of lung recoil could account for the reduction in resting airways dimensions in 7 of the 17 patients. Enhanced airway collapsibility commonly contributed to reduction in maximum flow. In three patients the airflow obstruction could be entirely accounted for by loss of lung recoil and enhanced airway collapsibility.